The Comparative Study of Social Participation between State and Non-profit High School Students in Yazd and Its Relevant Factors - SeyedAlireza Afshani; Akram Janatifar (جامعه شناسی کاربردی, 2016)
Introduction: Social participation is one of the important and constructive factors of Social capital. Social participation is defined as a kind of purposeful act during an interactional process between the actor and social environment for achieving the defined and predestinate aim. Despite the broad and in-depth discussions about social participation, it can be claimed that a general theory on all or most of variables related to participation remained to be developed. Obviously, it doesn't mean that no conceptual model can describe the participation. Although various theories have been proposed to explain the social participation, a model for predicting the different levels of social participation has not been represented yet. Furthermore, students are builders of the future for every society, and paying attention to them, in particular their participation, has great importance for themselves and their society. The present study compares the level of social participation between the students of state and non-profit high schools in Yazd as well as its related factors.   Material & Methods: This survey study is practical in terms of content, cross-sectional, and extensive. In the current study, the population was all junior high school students who attend state schools and nonprofit schools in Yazd. According to the statistical outcome measured by the Department of Education of Yazd, 7421 students were in state schools, and 3290 were in nonprofit schools. The Sampling method which applied in this survey study is a sampling of 642 state and nonprofit school students in Yazd (310 students from state schools and 332 students from nonprofit schools) Owing to collecting the data, participants filled out a questionnaire. A combination of stratified sampling method and cluster sampling method was applied. Owing to collecting the data, participants filled out a questionnaire. The validity of the data collection tool was ensured through a content validity and its reliability through a Cronbach's alpha. The Cronbach's alpha measured for the main variable was 0.901, and it measured for independent variables as follows: 0.747 for using mass media, 0.810 for social trust, 0.833 for normative integration, 0.805 for religiousness, 0.703 for fatalism and 0.744 for social alienation. The gleaned data were analyzed by the statistical software's, namely SPSS 22.   Discussion of Results & Conclusions: More than half of the participants were girls (51.4%) The average age of the participants was 16. In addition, of all the participants 34.9% in the first grade, 24.9% in second grade, 24.5% in third grade, and 15.7% in fourth grade were enrolled. The mean score was 63 for the main variable (social participation) Also, the score of social participation was mostly moderate. The mean score measured for the dependent variables as follows: using mass media = 16.71, social trust = 46.80, religiousness = 46.04, normative integration = 17.63, social alienation = 58.98 and fatalism = 19.36. Findings showed that there was a significant difference between social participation of nonprofit and state high school students. There was a significant and direct relationship between the variables including the level of mass media, social trust, religiousness, and normative Integration with social participation; however, there was a significant and reverse relationship between variables including socioeconomic status and social alienation with social participation. There was not any significant relationship between the variables of gender and fatalism with social participation. The results of multiple regression support the significant role of grade, socioeconomic status, mass media, social trust, religiousness, social alienation in social participation. Furthermore, through variance of the linear combination of the independent variables, 41 percent of the variance in social participation was explained.